Kejutan suhu pada penetasan telur dan sintasan hidup larva ikan lele (Clarias gariepinus) - Aer, Christo V.S; Mingkid, Winda M; Kalesaran, Ockstan J (Universitas Sam Ratulangi, 2015)
The aim of this study was determine the effect of temperature shock on hatching capability of the catfish eggs and its larval survivals.The study was conducted at the Board of Freshwater Aquaculture (BBAT ) in Tatelu Dimembe District, North Minahasa Regency, North Sulawesi Province. Twelve tanks were set in this experiment. Two hundred (200) eggs were put in each tank with controlled temperature of 25 C, 27 C , 29 C , and 32 ºC. Each temperature was replicated 3 times. The experimental design used in data analysis was completely randomized design (CRD). The results showed that the treatment temperature showed significant effect on hatching of eggs, while the difference in temperature had no effect on the survival rate of catfish larvae. Keywords: Temperature shock, eggs, hatching capability, survival rate, larvae, Clarias gariepinus.